Lichen Planus - Boch, Katharina; Langan, Ewan A.; Kridin, Khalaf; Zillikens, Detlef; Ludwig, Ralf J.; Bieber, Katja (Frontiers in Medicine, 2021)
Lichen planus (LP) is a T cell-mediated disease affecting the stratified squamous epithelia of the skin and/or mucus membrane. Histologically, the disease is characterized by a lichenoid inflammatory infiltrate and vacuolar degeneration of the basal layer of the epidermis. LP has three major subtypes: Cutaneous LP, mucosal LP and appendageal LP lichen planopilaris (LP of the scalp and other hair-bearing regions). Rarely, it may affect the nails in the absence of skin and/or mucosal changes. LP may also be induced by several drugs, typically anti-hypertensive medication or be associated with infections, particularly viral hepatitis. The diagnosis is based on the clinical presentation and characteristic histological findings. Although the disease is often self-limiting, the intractable pruritus and painful oral mucosal erosions result in significant morbidity. The current first-line treatment are topical and/or systemic corticosteroids. In addition, immunosuppressants may be used as corticosteroid-sparing agents. These, however are often not sufficient to control disease. Janus kinase inhibitors and biologics (anti-TNF, anti-IL-12/23, anti-IL17) have emerged as novel future treatment options. Thus, one may expect a dramatic change of the treatment landscape of LP in the near future.